Influence of Reaction Kinetics on Magneto-Convective Flow Through Poro-Elastic Media with Nonlinear Thermal Radiation and Buoyancy Effects - Adesanya, Samuel O; Onanaye, Adeniyi S; Lebelo, Ramoshweu S (Contemporary Mathematics, 2025)
The influence of Arrhenius kinetics on magneto-convective flows in regulating temperature variation within the poro-elastic medium in several thermal, industrial, and engineering applications, such as the control of the hot molten, formation of crystals, cooling of nuclear reactors, filtration, and many more, is investigated in the present study. The exothermic nature of the chemical reaction based on Arrhenius, Sensitized, and Bimolecular kinetics suggests nonlinear heat and mass transfer. In this regard, governing equations are formulated for solid displacement in porous materials, fluid flow velocity, energy, and concentration with appropriate boundary conditions. Numerical solutions for nonlinear coupled dimensionless boundary value problems are obtained using the Spectral Chebyshev Collocation Method (SCCM) and Spectral Quasi-Linearization Method (SQLM). The two solutions are shown to be convergent. The results are further validated through the fourth-order Shooting-Runge-Kutta Scheme and presented in graphical and tabular forms. The significant contribution to knowledge in the present study reveals that the reaction parameter is an increasing function of solid displacement, flow velocity, temperature, and concentration. Similarly, increasing fluid activation energy and buoyancy values encourage solid displacement, maximum flow velocity, and temperature distribution within the flow channel while decreasing nanoparticle concentration.